CASE REPORTSOperative treatment of tetralogy of Fallot with concomitant correction of anomalous origin of the left pulmonary artery from Kommerell’s diverticulum - Juscinski, Jacek; Haponiuk, Ireneusz; Chojnicki, Maciej; Steffens, Mariusz; Szofer-Sendrowska, Aneta; Jaworski, Radoslaw; Kwasniak, Ewelina; Żelechowski, Pawel (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Anomalies in development of the pulmonary valve, pulmonary trunk and peripheral pulmonary arteries are typical accompanying pathologies in patients with tetralogy of Fallot (ToF). Demanding for diagnostics and borderline for treatment is a condition colloquially called “discontinuous pulmonary arteries”, while the main branches are supplied with systemic blood from the ascending aorta, aortic arch or descending thoracic aorta. We present a case of a one-year-old girl with ToF and anomalous origin of the left pulmonary artery (LPA) from Kommerell’s diverticulum who underwent two-stage surgical therapy with the support of interventional cardiology. We conclude that early diagnosis of discontinuous pulmonary artery is crucial for choosing the optimal operative strategy. In our opinion, simultaneous anatomic intracardiac correction with direct pulmonary reconstruction seems reasonable and effective, particularly when the result is achieved after joint efforts of cardiac surgery and interventional cardiology.